Reactions of Micronutrient Metal Ions with Urinary Stone Forming Minerals - MAHAPATRA (CHOUDHURY), BASABI; SIDDIQUI, NAGMA; KUMAR, ASHISH; RANI SINHA, MADHU (Asian Journal of Chemistry, 2010)
Micronutrient metal ions were added to the inhibitor solutions of different amino acids such as glycine, β-alanine, L-cystine and hippuric acid with a view to study the increase or decrease of the inhibition efficiency of mineralization of urinary sone forming minerals. Micronutrient metal ions increase the inhibition up to some extent.